Non-clinical factors influencing the selection of patients with acute coronary syndromes for angiography. Issue 945 (14th July 2004) - Quaas, A; Curzen, N; Garratt, C
Abstract : Objective: To analyse clinical and non-clinical factors determining the selection for coronary angiography in patients with acute coronary syndromes (ACS). Design: Single centre, prospective cohort study. Participants: Eighty consecutive patients admitted with a diagnosis of ACS during the period 21 May 2001 to 4 July 2001. Setting: Coronary care unit of a tertiary referral centre, the Manchester Royal Infirmary. Data collection: Information concerning baseline patient characteristics, clinical presentation, and the selection for angiography was collected from the patient notes. Data analysis: Windows SPSS version 9.0 using cross tabulations with χ 2 estimation and binomial logistic regression analysis. Main outcome measure: Selection for angiography in ACS. Results: Cross tabulations with χ 2 analysis and logistic regression analysis identified significant non-clinical factors predicting the use of angiography. Although clinical factors such as recurrent ischaemia (odds ratio 5.11) influenced the decision to undergo coronary angiography, non-clinical factors such as young age (odds ratio 6.88 for <65 years old), gender (odds ratio 3.81 for males), admission on a weekday (odds ratio 0.2488 for admission on the weekend), and consultant in charge (odds ratio 0.111 for consultant "2") independently predicted the use of angiography in ACS. Conclusion: The selection of patients for angiography in ACS is not based purely on clinical criteria. Awareness of the apparent sources of bias among clinical decision makers may improve management of these patients.